PERAN BPSK DALAM PENYELESAIAN SENGKETA KONSUMEN DI INDONESIA UNTUK SEBAGAI WUJUD CITA-CITA PERLINDUNGAN KONSUMEN DI BIDANG EKONOMI - Imelda Tamba (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2018)
The main task of the Consumer Dispute Settlement Agency (BPSK) in accordance with Law Number 8 of 1999 concerning Consumer Protection is to deal with and resolve disputes between business actors and consumers. The function of BPSK is to handle and resolve consumer disputes outside the court. The Consumer Dispute Settlement Agency is an independent body, free from the influence and power of the Government and not under the structure of one Department or government institution, so that the BPSK assembly in carrying out its duties and authorities has full freedom and independence to make decisions in resolving consumer disputes objectively based on Law Number 8 of 1999 concerning Consumer Protection, and the Regulations for its implementation.